Elaboração de um manual de procedimentos para experimentos práticos em mecânica dos sólidos para obtenção do módulo de elasticidade - Pires, Felipe Alves (2014)
This work presents a manual of procedures to assemble practical experiments in order to obtain the Young’s Modulus of the materials and also to observe how these materials deform when forces are applied to them. To be able to do so, the conceptualization of this mechanical property and the theory that is linked to the Hooke’s law and Stress-Strain curve were considered here so that it was possible to collect the data and compare them to the theoretical values.